EU minimum wages: To what extent does ideology matter? - Sánchez-Vellvé, Francisco; León, Manuel (Estudios de Economía, 2021)
This paper estimates the importance of the political and ideological position of the ruling party in determining the minimum wage in the European Union Member States. To this end, a database that establishes the position of each government in each country and year is built. Using the panel data methodology, we conclude that the center-right governments tend to have lower relative minimum wages. The same result is found when the Chapel Hill Expert Survey policy indexes the are used. Ideology does not discriminate between conservative or liberal governments due to both of them setting minimum wages at similar levels, though lower than governments of social ideology.